2020
DOI: 10.1002/path.5380
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Neuropilin‐1 expression is an independent marker of improved survival in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) treatment has improved in the last decade with the introduction of drugs targeting tumor angiogenesis. However, the 5‐year survival of metastatic disease is still only 10–15%. Here, we explored the prognostic significance of compartment‐specific expression of Neuropilin 1 (NRP1), a co‐receptor for vascular endothelial growth factor (VEGF). NRP1 expression was analyzed in RCC tumor vessels, in perivascular tumor cells, and generally in the tumor cell compartment. Moreover, complex for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
(46 reference statements)
2
12
0
Order By: Relevance
“… 5 However, the understanding of mechanisms behind signaling pathways orchestrating tumor angiogenesis in RCCC should be thoroughly probed. 6 …”
Section: Introductionmentioning
confidence: 99%
“… 5 However, the understanding of mechanisms behind signaling pathways orchestrating tumor angiogenesis in RCCC should be thoroughly probed. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Antibodies against NRP1, RGS5, FOXM1, ROR2, and GALNT10 were selected for IHC analysis (see supplementary material, Figure S2 ) [ 27 , 28 , 29 , 30 , 31 ]. Of 138 cases, IHC was performed successfully for 131 (94.9%) cases in the discovery cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that patients with ccRCC had a poor prognosis. The 5-year survival rate of ccRCC patients is about 60%, which is lower than other types of RCC patients 3 - 5 .…”
Section: Introductionmentioning
confidence: 78%